The image of Asiatic Achaemenid empire according to the conversation of Lysis by Plato - Farzad Rafieifar; Esmaeil Sangari; Seyed Masoud Seyed Bonakdar (تاریخ نگری و تاریخ نگاری)
The Socratic conversation of "Lysis" is one of the first works of Plato. In this conversation Achaemenid empire and issues related to it were mentioned twice. At first, the great Achaemenid king with his domination of Asia and his legacy to his son are mentioned. It is also written about Darius I and her wealth in this conversation. The purpose of this article is to reflect on some of the images and appearance of the Achaemenid Empire in the minds of its contemporaries. From this point of view, in this article, only one of these two cases, namely Plato's words about rulership and dominion of the great king of Persia over the entire land of Asia, has been studied. This research, through a critical reading of "Lysis" and a several contemporary Achaemenid Greek texts, tries to investigate what ideas caused the image and concept of the Persian king dominating Asia in the minds of the Greeks of the 5th and 4th centuries BC to be created.